2001
DOI: 10.1159/000046956
|View full text |Cite
|
Sign up to set email alerts
|

Very High Daily Intraperitoneal Doses of Carbonyl Compounds Affect the Morphology, but Not the Exchange Characteristics, of Rat Peritoneum

Abstract: Glucose degradation products (GDP) are carbonyl compounds, that are formed by heat sterilization of conventional peritoneal dialysis (PD) fluids. Carbonyl compounds are known to be toxic in vitro and potentially toxic also in vivo. The aim of this study was to evaluate the effects of daily, short-term exposure of the peritoneum to very high concentrations of GDP in vivo on peritoneal transport parameters and on peritoneal morphology in a well-established rat model of PD. Rats were exposed to three daily intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Some reports have suggested that the decrease of ultrafiltration during peritoneal dialysis may be related to GDPs (25). Other in vivo investigation showed that elimination of these substances from the conventional acidic fluid did not change ultrafiltration and mass transfer area coefficient for glucose and 51 Cr‐EDTA but decreased these parameters in neutral solution (12). In the present transport analyses, we have studied the direct influence of glucose and methylglyoxal (one of the GDPs forming mainly during the heat sterilization of conventional peritoneal dialysis fluids) on the diffusive permeability of the peritoneum for icodextrin, in the separate experimental series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports have suggested that the decrease of ultrafiltration during peritoneal dialysis may be related to GDPs (25). Other in vivo investigation showed that elimination of these substances from the conventional acidic fluid did not change ultrafiltration and mass transfer area coefficient for glucose and 51 Cr‐EDTA but decreased these parameters in neutral solution (12). In the present transport analyses, we have studied the direct influence of glucose and methylglyoxal (one of the GDPs forming mainly during the heat sterilization of conventional peritoneal dialysis fluids) on the diffusive permeability of the peritoneum for icodextrin, in the separate experimental series.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the aforementioned studies, GDPs alone caused a significant decrease of thickness of rat submesothelial peritoneal tissue during 9 days. Neither differences in peritoneal cell density nor signs of interstitial fibrosis were observed (12). In other investigation, the number of human peritoneal mesothelial cells in GDP‐treated cultures was reduced by nearly 60% after 36 days (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a discrepancy might be due to the study design and the difference in the pH level. Musi et al [36]studied the effect of high concentration GDPs on thickening of the peritoneum, in which the GDP concentrations were 100 times more than conventional PDFs. Surprisingly, the peritoneum exposed to 100 times concentrated GDP solution was thinner than that exposed to non-GDP PDF.…”
Section: Discussionmentioning
confidence: 99%
“…However, in acute rat experiments, no negative effects of GDPs were observed with respect to peritoneal solute transport [permeability surface area product (PS) for glucose and Cr–ethylenediamine tetraacetic acid (EDTA)] and to UF properties, at least when pH was kept at 5.5 (12). This situation also held true when rats were exposed for 3 weeks to daily injections of PD fluid containing very high concentrations of GDPs (13). The only significant alteration occurring in peritoneal transport properties, after massive, short-term exposure to GDP-containing solutions, was a slight reduction in peritoneal lymph flow.…”
mentioning
confidence: 84%